First Genome Sequence of a Mexican Multidrug-Resistant Acinetobacter baumannii Isolate - Graña-Miraglia, Lucía (Genome Announc, 2016)
Acinetobacter baumannii has emerged as an important nosocomial pathogen worldwide. Here, we present the draft genome of the first multidrug-resistant A. baumannii isolate, sampled from a tertiary hospital in Mexico City. This genome will provide a starting point for studying the genomic diversity of this species in Mexico.